1986
DOI: 10.1017/s0022112086000721
|View full text |Cite
|
Sign up to set email alerts
|

Response behaviour of hot wires and films to flows of different gases

Abstract: Measurements of the voltage output for hot-wire and film anemometers placed in flows of nine different gases have been made as a function of flow velocity. It has been possible to correlate the measurements quite accurately by treating the data in terms of suitably defined Reynolds and Nusselt numbers. In order to obtain these correlations it has been necessary to consider and correct for the effects of probe-end conduction losses, temperature dependencies of gas molecular properties, flow slip at the probe su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In other words, the local heat transfer rate q,. This is essentially extending the route of Pitts and McCaffrey (1986) to account for the correction due to the dependence of the Nusselt number on the temperature difference. between the wire and the ambient fluid alone, an observation supported through Fig.…”
Section: Revision Of the Theoretical Frameworkmentioning
confidence: 99%
“…In other words, the local heat transfer rate q,. This is essentially extending the route of Pitts and McCaffrey (1986) to account for the correction due to the dependence of the Nusselt number on the temperature difference. between the wire and the ambient fluid alone, an observation supported through Fig.…”
Section: Revision Of the Theoretical Frameworkmentioning
confidence: 99%
“…It was discovered that none of these correlations were successful in correlating an extensive series of calibrations performed in ten different gases [11,12]. The most widely quoted correlation for different gases utilized a correction based on the Prandtl number (Pr) to correct for variations in molecular properties [13][14][15] .…”
Section: Simultaneous Concentration and Velocity Measurementmentioning
confidence: 99%
“…Extensive analysis [11,12] of the data showed that it is necessary to consider the temperature dependence of the molecular properties in order to obtain accurate correlations. Other heat transfer characteristics such as thermal slip and surface accommodation were also investigated during the course of this study [11,12].…”
Section: Simultaneous Concentration and Velocity Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The manuscripts which resulted from this work [10,11,12] are not only significant for their importance to researchers who wish to utilize HWA in different gases, but are also important for the much wider field of heat transfer.…”
Section: Research Accohflishmentsmentioning
confidence: 99%